Mastering Digital Literacy - ALCOCK, Marie (Contemporary Perspectives on Literacy, 2014)
Schools must prepare 21st century students to compete in a global society a world in which cultures, economies, and people are continuously connected, and it is the job of educators to equip students to meet this challenge. In the Contemporary Perspectives on Literacy series, editor Heidi Hayes Jacobs and a team of authors from around the globe explore the three new literacies global, media, and digital literacy.